New trends in developmental coordination disorder: Multivariate, multidimensional and multimodal - Ke, Li; Su, Xueting; Yang, Sijia; Du, Zhihao; Huang, Shunsen; Wang, Yun (Frontiers in Psychiatry, 2023)
Developmental Coordination Disorder (DCD) is a motor development disorder that affects an individual’s growth and development, and may persist throughout life. It is not caused by intellectual or physical disability. Studies have suggested DCD often occurs in childhood, resulting in a series of abnormal manifestations that hinder children's normal development; cohort studies suggest a higher incidence in boys than in girls. Early diagnosis and appropriate interventions can help relieve symptoms. Unfortunately, the relevant research still needs to be further developed. In this paper, we first start from the definition of DCD, systematically investigate the relevant research papers in the past decades and summarize the current research hotspots and research trends in this field. After summarizing, it is found that this research field has attracted more researchers to join, the number of papers published has increased year by year and has become a hot spot in multidisciplinary research, such as education, psychology, sports rehabilitation, neurobiology, and neuroimaging. The continuous development of the correlation between perinatal factors and DCD, various omics studies, and neuroimaging methods also brings new perspectives and working targets to DCD research. DCD-related research will continue to deepen along the research direction of multivariate, multidimensional, and multimodal.